Penggunaan Berbagai Dosis Pupuk Kandang Terhadap Pertumbuhan Bibit Sukun (Artocarpus communis. Forst) pada DTA Danau Toba - Chaerul Parsaulian Ginting; Afifuddin Dalimunthe; Budi Utomo (Peronema Forestry Science Journal, 2015)
This research aims to  know the  best dose  of  fertilizer  (chicken  manure) in the growth of breadfruit as land rehabilitation efforts) in the catchment area of Lake Toba Haranggaol horison district. The method used in this study is a randomized block design (RBD) non factorial with 11 treatments and 4 replications. The parameters used in this study are as height, diameter, number of leaves, leaf area, crown area and leaf water content. The  results  showed the  addition of manure  can  provide  good  growth response to breadfruit plant. In various parameters showed dose of chicken manure 700 and 800 gr give a better effect than the other doses. Analysis of   variance ANOVA showed dose of  chicken manure does not provide significant effect on the growth of breadfruit plant.Key word: critical land, breadfruit, dose of chicken manure, Lake Toba Catchment Area